Implementing managed alcohol programs in hospital settings: A review of academic and grey literature. (18th January 2018) - Brooks, Hannah L.; Kassam, Shehzad; Salvalaggio, Ginetta; Hyshka, Elaine
Abstract: Issues: People with severe alcohol use disorders are at increased risk of poor acute‐care outcomes, in part due to difficulties maintaining abstinence from alcohol while hospitalised. Managed alcohol programs (MAP), which administer controlled doses of beverage alcohol to prevent withdrawal and stabilise drinking patterns, are one strategy for increasing adherence to treatment, and improving health outcomes for hospital inpatients with severe alcohol use disorders. Approach: Minimal research has examined the implementation of MAPs in hospital settings. We conducted a scoping review to describe extant literature on MAPs in community settings, as well as the therapeutic provision of alcohol to hospital inpatients, to assess the feasibility of implementing formal MAPs in hospital settings and identify knowledge gaps requiring further study. Four academic and 10 grey literature databases were searched. Evidence was synthesised using quantitative and qualitative approaches. Key Findings: Forty‐two studies met review inclusion criteria. Twenty‐eight examined the administration of alcohol to hospital inpatients, with most reporting positive outcomes related to prevention or treatment of alcohol withdrawal. Fourteen studies examined MAPs in the community and reported that they help stabilise drinking patterns, reduce alcohol‐related harms and facilitate non‐judgemental health and social care. Implications/Conclusions: MAPs in the community have been well described and research has documented effective provision of alcohol in hospital settings for addressing withdrawal. Implementing MAPs as a harm reduction approach in hospital settings is potentially feasible. However, there remains a need to build off extant literature and develop and evaluate standardised MAP protocols tailored to acute‐care settings.